Hospital Management System Core Transaction 3 (Bed and Linen Management, Homis Analytics, Medical Package With Online Based Pharmacy): Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
One of the many struggles every growing company faces is choosing the best system tomanage its business operations. At first, buying several stand-alone tools may seem cheaperand more effective than purchasing a complete software solution. As a consequence, acompany uses several different applications that do not cooperate, making it impossible foremployees to work effectively and for the company to prosper. (Drew's editorial team, July2022) The development team focused on benefitting hospitals by reducing expenses anddelaying work issues. It also helps to give convenience to both patients and staff; Inaccuracyand outdated data will be prevented, and the productivity of hospital workers will increase. Theproject team proposed a new method in which the Hospital will be using a web-basedintegration system that aims to help the hospital, especially the core transactions, to managehospital operations such as Bed and linen management, HOMIS analytics, medical package,and pharmacy. To accomplish these objectives.As a result, the system helps users in their work, such as recording stocks, updating records,viewing real-time analytics, and displaying medical packages. It also enabled nurses,housekeepers, and pharmacists to operate productively and manage patients in a hassle-freemanner. Patients can now buy their medical supplies online without going to a physical store.Our project study discussed the core transactions of the Hospital Management System. It isdeveloped through the help of stakeholders to meet the standards of the clients.
Keywords: IT & Management